Evidence on the Benefits of Alternative Mortgage Products - COCCO, JOÃO F. (Journal of Finance, 2013)
ABSTRACT Alternative mortgage products have been identified by many as culprits in the financial crisis. However, because of their lower initial mortgage payments relative to loan amount, they may be a valuable tool for households that expect higher and more certain future labor income, and that wish to smooth consumption over the life‐cycle. Using U.K. household‐level panel data, this paper provides evidence in support of this hypothesis and highlights other important benefits of alternative mortgages, including portfolio diversification, tax benefits, and a reduction in the transaction costs incurred in housing transactions.